O uso indiscriminado da proporcionalidade como carência de fundamentação: risco à democracia - Locatelli, Alexandre Lagoa (2021)
The present work, which will be developed by the deductive method, with literature review of national and foreign authors, intends to discuss the unmotivated use of proportionality and what are its risks to democracy. It’s expected, as a result, to answer the research problem, if unmotivated decisions, especially by the use of proportionality of open principles, hurt the power functions separation and what are the possible risks. Proportionality is a technique often used to pondering principles, but it is often used as a mere argumentative reinforcement, without due motivation. The objective is to understand why this occurs, as well as to analyze its consequences The study begins with the democracy institute, to understand the importance of the separation of power functions and its limitation. After, the legitimacy of the Judiciary power and the importance of the reasoning to guarantee it will be analyzed. Finally, proportionality will be entered specifically, understanding its requirements, the scenario of the expanding use of principles and the consequent need to pondering them, as well as verifying whether proportionality is correctly applied by the Supremo Tribunal Federal. As results, it will be possible to verify a low index of adequate reasoning when using proportionality, also its danger, since without it a magistrate may decide public policy issues, typical of the Legislative or Executive, sometimes against infraconstitutional laws, based on use of proportionality. Thus, there is an enormous risk for the institutional arrangement, since the Judiciary, which should contain the advance of other powers, is precisely overcoming, invading the competence sphere of another power and endangering the democratic stability.